Mg-Ag-Sb ternary compound single crystal material with low thermal conductivity and preparation method thereof
By preparing a single crystal material with low thermal conductivity Mg-Ag-Sb ternary compound, the complex phonon transport problem caused by crystal defects in polycrystalline materials in the prior art is solved, and the preparation of single crystal materials with high purity and low thermal conductivity is achieved, which is suitable for the field of thermoelectric and thermal barrier coatings.
Patent Information
- Application Number
- CN202411751062.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
The research on the existing technology of medium and low thermal conductivity materials is mainly focused on polycrystalline samples. Various high-concentration crystal defects exist in the polycrystalline materials, which complicates the understanding of intrinsic phonon transmission and lacks to study phonon transmission in single crystal materials with intrinsic low thermal conductivity.
A single crystal material with high purity and uniformity of Mg-Ag-Sb ternary compound is adopted and its preparation method. Through the steps of raw material weighing, packaging, single crystal growth and centrifugation, a single crystal material with high purity and uniformity is prepared.
The prepared Mg-Ag-Sb ternary compound single crystal material has extremely low thermal conductivity, high purity and uniformity of the material, and is suitable for thermal barrier coatings and thermoelectric fields.
Smart Images

Figure CN119710892A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor crystal materials, and in particular relates to a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material and a preparation method thereof. Background Art
[0002] Low thermal conductivity materials can provide insulation, prevent heat transfer and control heat flow, and have important application value in thermal barrier coatings and thermoelectrics. The characteristics of such materials include high average atomic weight, weak bonding, and highly disordered and distorted structure. These characteristics also indicate possible directions for regulating thermal conductivity.
[0003] Heat transfer in insulating materials is mainly through phonon transmission (i.e., lattice vibration). Enhancing phonon scattering can significantly reduce the mean free path of phonons, which can effectively suppress thermal conductivity. Therefore, by adjusting the level of phonon scattering, the thermal conductivity of the material can be regulated, which can be achieved by changing the composition, microstructure and interface design of the material. For example, point defects (such as substitutional point defects generated by aliovalent doping and isoelectronic alloying, interstitials and vacancies), dislocations, interfaces (such as grain boundaries, superlattices, etc.), and nanostructures (such as nanoparticles and nanoprecipitates, etc.) can be used to enhance phonon scattering and thus reduce the thermal conductivity of the material.
[0004] Previous studies on low thermal conductivity materials have focused on polycrystalline samples due to the ease of preparation of polycrystalline materials. However, polycrystalline materials inevitably contain various high concentrations of crystal defects, which often introduce additional scattering and complicate the understanding of intrinsic phonon transport. Therefore, it would be very meaningful to study phonon transport in single-crystalline materials with intrinsic low thermal conductivity. Summary of the invention
[0005] The purpose of the present invention is to overcome at least one of the deficiencies of the above-mentioned prior art and to provide a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material and a preparation method thereof. The prepared single crystal material has high purity and uniformity and extremely low thermal conductivity.
[0006] The technical solution of the present invention is: a method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material, comprising the following steps:
[0007] Raw material weighing step: weigh Mg, Ag, Sb and Bi raw materials according to the set stoichiometric ratio;
[0008] Packaging step: packaging the raw materials weighed in the raw materials weighing step in a packaging container;
[0009] Single crystal growth step: placing the packaging container in a temperature control device for temperature control, so that the raw materials in the packaging container are completely melted to form a melt and then cooled, so that a crystal embryo is formed in the melt and grows into a single crystal;
[0010] Centrifugation step: the temperature of the melt in the packaging container drops to a set range, and the packaging container is placed in a centrifugal device for centrifugal treatment, so that the single crystals in the melt are separated to obtain Mg-Ag-Sb ternary compound single crystal material.
[0011] Optionally, in the raw material weighing step, the stoichiometric ratio of Mg, Ag, Sb and Bi is 1:x:y:z, wherein x=0.5 to 6, y=0.5 to 15, and z=0.5 to 70.
[0012] Optionally, in the raw material weighing step, the content of Bi element is higher than the content of Sb element.
[0013] Optionally, the packaging step includes a first packaging step: Mg, Ag, Sb and Bi raw materials are mixed and placed in a heat-resistant container, and the heat-resistant container is packaged under an inert gas atmosphere, and the packaging container includes a heat-resistant container.
[0014] Optionally, the temperature-resistant container is a tantalum tube or a niobium tube, and the tantalum tube or the niobium tube is packaged by a packaging device; the packaging device is a tungsten inert gas welding device.
[0015] Optionally, the packaging container further includes a protective container, and the packaging step further includes a second packaging step:
[0016] The packaged temperature-resistant container is placed in a protective container, and the protective container is packaged under vacuum conditions.
[0017] Optionally, in the packaging step, a filter is provided in the temperature-resistant container, and the filter is provided above the raw materials.
[0018] Optionally, in the temperature control step, the temperature control device is heated from room temperature to 900 to 1000°C at a heating rate of 5 to 15°C / min; kept at 900 to 1000°C for 5 to 72 hours to completely melt the raw materials in the packaging container and mix them evenly; and slowly cooled to 450 to 700°C at a cooling rate of 1 to 20°C / min.
[0019] Optionally, the rotation speed of the centrifugal device is 500 to 2000 r / min, and the centrifugation time is 1 to 3 min.
[0020] The present invention also provides a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material, which is prepared by the above-mentioned method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material.
[0021] The present invention provides a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material and a preparation method thereof. The single crystal thermoelectric material can be Mg4.8 Ag 1.4 Sb4 single crystal material can be prepared by the above-mentioned single crystal thermoelectric material preparation method. In the embodiment of the present invention, Bi is mixed with high-purity Mg, Ag, and Sb elements as a co-solvent and placed in a tantalum tube (or niobium tube), and the tantalum tube (or niobium tube) is encapsulated under an argon atmosphere, and then the tantalum tube (or niobium tube) is placed in a quartz tube, and the quartz tube is encapsulated under a vacuum environment. The quartz tube is then placed in a pit furnace, heated to a certain temperature and kept warm for a period of time. After all the raw materials are melted, the temperature is slowly lowered. As the temperature drops, the supercooling in the melt continues to increase, accompanied by the appearance of a crystal embryo. The temperature is further reduced, and the crystal embryo gradually grows into a single crystal. After it drops to a certain temperature, the quartz tube is taken out and inverted into a centrifuge for centrifugation to separate the single crystal from the melt. The preparation method has strong controllability, and the prepared material has high purity and uniformity, and extremely low thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 Mg prepared in Example 1 of the present invention 4.8 Ag 1.4 Physical picture of Sb4 single crystal, single crystal quality picture and crystal structure picture;
[0024] Figure 2 Mg prepared in Example 1 of the present invention 4.8 Ag 1.4 Scanning electron microscopy characterization of Sb4 single crystal;
[0025] Figure 3 Mg prepared in Example 1 of the present invention 4.8 Ag 1.4 Electrical properties and bandgap width diagram of Sb4 single crystal;
[0026] Figure 4 Mg prepared in Example 1 of the present invention 4.8 Ag 1.4 Thermal properties diagram of Sb4 single crystal. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0028] It should be noted that the terms “setting” and “connection” should be understood in a broad sense. For example, it can be directly setting or connecting, or it can be indirectly setting or connecting through a central component or a central structure.
[0029] In addition, in the embodiments of the present invention, if there are terms indicating orientation or positional relationships such as "longitudinal", "transverse", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., they are based on the orientation or positional relationships or conventional placement states or usage states shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the structure, feature, device or element referred to must have a specific orientation or positional relationship, nor must it be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of the present invention, unless otherwise specified, "multiple" means two or more.
[0030] The various specific technical features and embodiments described in the specific implementation methods can be combined in any suitable manner unless there is any contradiction. For example, different implementation methods can be formed by combining different specific technical features / embodiments. In order to avoid unnecessary repetition, the various possible combinations of the specific technical features / embodiments in the present invention will not be described separately.
[0031] like Figure 1 and Figure 2 As shown, a method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material provided by an embodiment of the present invention comprises the following steps:
[0032] Raw material weighing step: weigh Mg, Ag, Sb and Bi raw materials according to the set stoichiometric ratio;
[0033] Packaging step: packaging the raw materials weighed in the raw materials weighing step in a packaging container;
[0034] Single crystal growth step: placing the packaging container in a temperature control device for temperature control, so that the raw materials in the packaging container are completely melted to form a melt and then cooled, so that a crystal embryo is formed in the melt and grows into a single crystal;
[0035] Centrifugation step: the temperature of the melt in the packaging container drops to a set range, and the packaging container is placed in a centrifugal device for centrifugal treatment, so that the single crystals in the melt are separated to obtain Mg-Ag-Sb ternary compound single crystal material.
[0036] In this way, a large amount of Mg, Ag, and Sb elements are dissolved in the Bi melt during high temperature preservation. Once the temperature starts to drop slowly, the solubility of these elements in Bi will decrease, resulting in supercooling. At this time, some embryos will appear in the melt. Continuing to cool down will further increase the supercooling, and the embryos will gradually grow into single crystals. The prepared material has high purity and uniformity, and extremely low thermal conductivity.
[0037] Specifically, in the step of weighing the raw materials, the stoichiometric ratio of Mg, Ag, Sb, and Bi is 1:x:y:z, wherein x=0.5 to 6, y=0.5 to 15, and z=0.5 to 70. In this embodiment, the Mg-Ag-Sb ternary compound single crystal material is Mg 4.8 Ag 1.4 Sb4 single crystal thermoelectric material, its room temperature thermal conductivity can be as low as ~ 0.6W m -1 K -1 Although the single crystal has a simple face-centered cubic structure, due to the Mg atoms ( ~ 60%), Ag atoms ( ~ 17.5%) and vacancies ( ~ 22.5%) mixed with Mg 4.8 Ag 1.4 The 8c site of Sb4 leads to a high degree of atomic occupancy disorder, resulting in a high anharmonic scattering rate and a short phonon mean free path inside it, which makes the thermal conductivity at an extremely low level.
[0038] Specifically, in the raw material weighing step, the purity of Mg, Ag, Sb, and Bi particles should be greater than 99.8%, the packaging container may include a tantalum tube or a niobium tube, and the content of the Bi element may be much higher than the content of the Sb element to prevent Sb from reacting with the tantalum tube or the niobium tube.
[0039] Specifically, the packaging step includes a first packaging step: Mg, Ag, Sb and Bi raw materials are mixed and placed in a heat-resistant container, and the heat-resistant container is packaged under an inert gas (which may be argon) atmosphere, and the packaging container includes a heat-resistant container.
[0040] Specifically, the heat-resistant container may be an inert metal tube such as a tantalum tube or a niobium tube, and the tantalum tube or the niobium tube is packaged by a packaging device; the packaging device may be a tungsten inert gas arc welding device. In specific applications, the tantalum tube or the niobium tube should be cleaned and kept dry in advance to avoid other impurities from being mixed into the raw materials. In specific applications, the raw materials can be first placed in a carbon tube or other tube that does not react with the raw materials, and then the carbon tube or other tube that does not react with the raw materials can be placed in a heat-resistant container (tantalum tube or niobium tube). In the present invention, a niobium tube is taken as an example.
[0041] Specifically, the packaging container further includes a protective container, and the packaging step further includes a second packaging step:
[0042] The encapsulated heat-resistant container is placed in a protective container, and the protective container is encapsulated under vacuum conditions. The protective container may be a quartz tube or the like. In specific applications, the vacuum environment may be obtained by vacuum generating equipment such as a mechanical pump or a molecular pump. The quartz tube is resistant to high temperatures and will not be oxidized at high temperatures, thereby protecting the tantalum tube or the niobium tube.
[0043] Specifically, in the packaging step, a filter is provided in the heat-resistant container, and the filter is provided above the raw material. In specific applications, in the first packaging step, a tantalum (or niobium) filter can be placed in a heat-resistant container (tantalum tube or niobium tube) and fixed above the raw material to facilitate the separation of more single crystals during the centrifugation process. In specific applications, the packaging container is inverted in a centrifugal device for centrifugal treatment. That is, after the temperature control step, the temperature of the raw material drops to a set range, and the quartz tube can be inverted in a centrifugal device for centrifugal treatment. Of course, the quartz tube can also be placed in a centrifugal device, and the centrifugal device inverts the quartz tube.
[0044] Specifically, the temperature control equipment can be a pit furnace, etc. The protective container (quartz tube) should be placed in the middle of the pit furnace as much as possible to ensure that the quartz tube is heated evenly in all directions, and to minimize the melt convection and single crystal composition unevenness caused by temperature differences. In the temperature control step, the temperature control equipment is heated from room temperature to 900 to 1000°C, and the heating rate is 5 to 15°C / min; it is kept at 900 to 1000°C for 5 to 72 hours to completely melt the raw materials in the packaging container and mix them evenly; it is slowly cooled to 450 to 700°C, and the cooling rate is 0.5 to 20°C / min or 1 to 20°C / min. In specific applications, the cooling program should be as slow as possible to obtain higher quality single crystals. In specific applications, the temperature can be raised to 950°C, 980°C, 1000°C, 1020°C, 1050°C or 1080°C, etc. in the heating stage. The heating rate can be 6°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min, etc. In the heat preservation stage, the temperature can be kept at 950°C, 980°C, 1000°C, 1020°C, 1050°C or 1080°C for 6h, 12h, 18h, 24h, 36h, 48h, 60h, etc. In the cooling stage, the temperature can be reduced to 480°C, 520°C, 560°C, 600°C, 640°C or 680°C, etc. The cooling rate can be 0.5°C / min, 0.8°C / min, 1.2°C / min, 1.5°C / min, 2°C / min, 3°C / min, etc.
[0045] Specifically, in the centrifugation step, the rotation speed of the centrifugal device is 500 to 2000 r / min, and the centrifugation time is 1 to 3 min.
[0046] The present invention also provides a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material, the single crystal thermoelectric material can be Mg 4.8 Ag 1.4 Sb4 single crystal material can be prepared by the above-mentioned single crystal thermoelectric material preparation method. In the embodiment of the present invention, Bi is used as a co-solvent and mixed with high-purity Mg, Ag, and Sb elements and then placed in a tantalum tube (or niobium tube), and the tantalum tube (or niobium tube) is encapsulated under an argon atmosphere, and then the tantalum tube (or niobium tube) is placed in a quartz tube, and the quartz tube is encapsulated under a vacuum environment. The quartz tube is then placed in a pit furnace, heated to a certain temperature and kept warm for a period of time. After all the raw materials are melted, the temperature is slowly lowered. As the temperature drops, the degree of supercooling in the melt continues to increase, accompanied by the appearance of a crystal embryo. The temperature is further reduced, and the crystal embryo gradually grows into a single crystal. After it drops to a certain temperature, the quartz tube is taken out and inverted into a centrifuge for centrifugation to separate the single crystal from the melt. The Mg 4.8 Ag 1.4 The preparation method of Sb4 single crystal thermoelectric material is highly controllable, the prepared material has high purity and uniformity, and extremely low thermal conductivity.
[0047] Example 1
[0048] According to the stoichiometric ratio of 1:1:1:10, 50 g of Mg, Ag, Sb, and Bi particles with a purity of 99.99% were weighed as raw materials;
[0049] Mix the raw materials and put them into the tantalum tube, then fix the circular tantalum filter above the raw materials, and ensure that the space from the filter to the tantalum tube mouth is enough to accommodate the flux Bi. Put the tantalum tube into the tungsten inert gas welding, evacuate and purge with argon gas several times, and then fill it with 50% to 98% argon gas, and then use a tungsten needle to start the arc and seal the tube mouth of the tantalum tube;
[0050] The packaged tantalum tube is placed in a quartz tube, and the quartz tube is installed in a vacuum tube sealing device, and a mechanical pump is used to evacuate the quartz tube, and the quartz tube is packaged in a vacuum environment;
[0051] Place the packaged quartz tube in the middle of the pit furnace and set the temperature program as follows: ① heat up from room temperature to 1000℃ at a heating rate of 15℃ / min; ② keep at 1000℃ for 12h to completely melt the raw materials and mix them evenly; ③ slowly cool down to 550℃ at a cooling rate of 2℃ / min;
[0052] The quartz tube was taken out at 550° C. and quickly inverted in a centrifuge for centrifugation at a speed of 1000 r / min for 2 min to separate the mixed solution of the co-solvent Bi and the solute from the single crystal.
[0053] Mg grown using high temperature Bi flux 4.8 Ag 1.4 Sb4 single crystal Figure 1 As shown in the inset of (a), the surface of the octahedral crystal has a silvery white metallic luster. The X-ray diffraction pattern of the single crystal is shown in Figure 1 As shown in (a), the single crystal surface is preferentially oriented along the (111) plane, which is consistent with the theoretical map (black solid line) generated from single crystal crystallography data. Figure 1 (b) is the rocking curve of the single crystal sample. The solid line represents the rocking curve of the (111) peak. 4.8 Ag 1.4 The full width at half maximum (FWHM) of Sb4 single crystal is only ~ 0.016°, indicating good crystallinity. Mg 4.8 Ag 1.4 The crystal structure of Sb4 is a typical antifluorite structure with a cubic space group. (No. 225), the crystal structure is as follows Figure 1 (c) shows that the gray octahedron composed of six Sb atoms is 4.8 Ag 1.4 Sb4 single crystal ( Figure 1 (Inset of (a)) have the same geometry. Figure 1 (d)-(f) are Mg when c=0, 1 / 4 and 1 / 2 respectively. 4.8 Ag 1.4 Two-dimensional electron density map of the ab plane of Sb4 single crystal, in which the 4b position is completely occupied by Sb atoms, while the 8c position is mixed with Mg and Ag atoms. In particular, the 8c position is not completely occupied by Mg and Ag atoms, and there are about 22.5% vacancies. The atomic ratio of Mg:Ag:Sb is determined to be about 4.8(8):1.36(2):4. The determined single crystal composition is consistent with the results of energy dispersive spectroscopy (EDS, Mg:Ag:Sb=48.8(2):13.5(3):37.6(5)) and electron probe microscopy analysis (EPMA, Mg:Ag:Sb=48.9(2):14.1(5):36.9(3)) in Table 1. Figure 2 Mg is shown 4.8 Ag 1.4 Scanning electron microscopy characterization of Sb4 single crystals shows that the generated single crystal bulk material has uniform composition and there is no segregation of Mg, Ag, and Sb. In summary, a dense and uniform Mg 4.8 Ag 1.4Sb4 single crystal thermoelectric material.
[0054] The mixed occupation of Mg, Ag and vacancies at the 8c site indicates that the compound is highly disordered, i.e., the concentration of point defects is high. Intuitively, such a large site disorder should greatly reduce the mobility of electrons and the mean free path of phonons, thus significantly deteriorating the electrical conductivity and suppressing the thermal conductivity. Figure 3 (a)-(c) are Mg 4.8 Ag 1.4 The electrical properties of Sb4 single crystal, in which the resistivity is two orders of magnitude higher than that of thermoelectric materials with better performance. At the same time, due to the extremely low mobility, the Seebeck coefficient is almost the same as that of thermoelectric materials with better performance, resulting in Mg 4.8 Ag 1.4 The electrical properties of Sb4 single crystal are very poor. There is almost no bipolar diffusion effect in the temperature range below 300K, which is mainly related to its large bandgap width ( Figure 3 (d)), is 1.37eV. Figure 4 Mg 4.8 Ag 1.4 Thermal properties of Sb4 single crystal, its room temperature thermal conductivity is as low as ~ 0.6W m -1 K -1 , the maximum thermal conductivity appears at 49K, which is ~ 0.93W m -1 K -1 Since the electronic thermal conductivity is very low and can be almost ignored, the thermal conductivity mainly depends on the lattice thermal conductivity.
[0055] Table 1: Mg 48 Ag 14 Energy dispersive spectroscopy and electron probe microscopy analysis results of Sb4 single crystal
[0056]
[0057] The embodiment of the present invention provides an ultra-low thermal conductivity Mg 4.8 Ag 1.4Sb4 single crystal thermoelectric material and its preparation method belong to the technical field of semiconductor crystal materials. First, Bi is used as a co-solvent and mixed with high-purity Mg, Ag, and Sb elements, and then placed in a tantalum tube (or niobium tube), and the tantalum tube (or niobium tube) is encapsulated in an argon atmosphere. Then the tantalum tube (or niobium tube) is placed in a quartz tube, and the quartz tube is encapsulated in a vacuum environment. The quartz tube is then placed in a pit furnace, heated to a certain temperature and kept warm for a period of time. After all the raw materials are melted, the temperature is slowly lowered. As the temperature drops, the degree of supercooling in the melt continues to increase, accompanied by the appearance of a crystal embryo. The temperature is further reduced, and the crystal embryo gradually grows into a single crystal. After it drops to a certain temperature, the quartz tube is taken out and inverted into a centrifuge for centrifugation to separate the single crystal from the melt. The Mg 4.8 Ag 1.4 The preparation method of Sb4 single crystal thermoelectric material is highly controllable, the prepared material has high purity and uniformity, and extremely low thermal conductivity.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material, characterized in that: The following steps are involved: Raw material weighing step: weigh Mg, Ag, Sb and Bi raw materials according to the set stoichiometric ratio; Packaging step: packaging the raw materials weighed in the raw materials weighing step in a packaging container; Single crystal growth step: placing the packaging container in a temperature control device for temperature control, so that the raw materials in the packaging container are completely melted to form a melt and then cooled, so that a crystal embryo is formed in the melt and grows into a single crystal; Centrifugation step: the temperature of the melt in the packaging container drops to a set range, and the packaging container is placed in a centrifugal device for centrifugal treatment, so that the single crystals in the melt are separated to obtain Mg-Ag-Sb ternary compound single crystal material.
2. The method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 1, characterized in that: In the raw material weighing step, the stoichiometric ratio of Mg, Ag, Sb and Bi is 1:x:y:z, wherein x=0.5 to 6, y=0.5 to 15, and z=0.5 to 70.
3. The method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 1, characterized in that: In the step of weighing the raw materials, the content of the Bi element is higher than the content of the Sb element.
4. The method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 1, characterized in that: The packaging step includes a first packaging step: Mg, Ag, Sb and Bi raw materials are mixed and placed in a heat-resistant container, and the heat-resistant container is packaged under an inert gas atmosphere, and the packaging container includes a heat-resistant container.
5. The method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 4, characterized in that: The temperature-resistant container is a tantalum tube or a niobium tube, and the niobium tube or the niobium tube is packaged by a packaging device; the packaging device is a tungsten inert gas arc welding device.
6. The method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 4, characterized in that: The packaging container further includes a protective container, and the packaging step further includes a second packaging step: The packaged temperature-resistant container is placed in a protective container, and the protective container is packaged under vacuum conditions.
7. The method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to any one of claims 1 to 6, characterized in that: In the packaging step, a filter is arranged in the temperature-resistant container, and the filter is arranged above the raw materials.
8. The method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 1, characterized in that: In the temperature control step, the temperature control device is heated from room temperature to 900 to 1000°C at a heating rate of 5 to 15°C / min; kept at 900 to 1000°C for 5 to 72 hours to completely melt and mix the raw materials in the packaging container; and slowly cooled to 450 to 700°C at a cooling rate of 1 to 20°C / min.
9. The method for preparing the low thermal conductivity Mg-Ag-Sb ternary compound single crystal material according to claim 1, characterized in that: The rotation speed of the centrifugal device is 500 to 2000 r / min, and the centrifugal time is 1 to 3 minutes.
10. A low thermal conductivity Mg-Ag-Sb ternary compound single crystal material, characterized in that: The material is prepared by the method for preparing a low thermal conductivity Mg-Ag-Sb ternary compound single crystal material as claimed in any one of claims 1 to 9.
Citation Information
Cited By
Intrinsic superlattice single crystal material and preparation method thereof
CN121931617A